Introduction to the Special Issue: European youth migration: human capital outcomes, skills and competences. - Lulle, Aija; Janta, Hania; Emilsson, Henrik (Journal of Ethnic & Migration Studies, 2021)
Human capital has been long an exceedingly important concept in migration research. Over time there have been attempts to provide more nuanced, and less economistic interpretations of human capital. Based on outputs from the EU Horizon 2020 project YMOBILITY (2015–2018) and two additional papers, this Special Issue seeks to advance this agenda further by addressing the complexities of the mobility of human capital. Migration problematises human capital assumptions due to challenges in transferring human capital across national borders. In this introductory paper we propose rethinking the human capital of migrants in a three-fold way. Firstly, we question the interpretation of skills and competences beyond the conventional divide of 'higher-skilled' and 'lower-skilled' through the concept of a 'knowledgeable migrant'. Secondly, we probe deeper into an understanding of the transferability of skills in relation to 'location', exploring the possibilities and constraints to the transfer of human capital in different spatial contexts. Thirdly, we theorise human capital in terms of new temporalities of migration and the role these play in skill acquisition. We illustrate our novel theoretical thinking with selected empirical data, both quantitative and qualitative, on youth mobility in Europe.